Association of the magnitude of weight loss and changes in physical fitness with long-term cardiovascular disease outcomes in overweight or obese people with type 2 diabetes: a post-hoc analysis of the Look AHEAD randomised clinical trial. Issue 11 (November 2016) - ,
Summary: Background: Findings from the Look AHEAD trial showed no significant reductions in the primary outcome of cardiovascular disease incidence in adults with type 2 diabetes randomly assigned to an intensive lifestyle intervention for weight loss compared with those randomly assigned to diabetes support and education (control). We examined whether the incidence of cardiovascular disease in Look AHEAD varied by changes in weight or fitness. Methods: Look AHEAD was a randomised clinical trial done at 16 clinical sites in the USA, recruiting patients from Aug 22, 2001, to April 30, 2004. In the trial, 5145 overweight or obese adults aged 45–76 years with type 2 diabetes were assigned (1:1) to an intensive lifestyle intervention or diabetes support and education. In this observational, post-hoc analysis, we examined the association of magnitude of weight loss and fitness change over the first year with incidence of cardiovascular disease. The primary outcome of the trial and of this analysis was a composite of death from cardiovascular causes, non-fatal acute myocardial infarction, non-fatal stroke, or admission to hospital for angina. The secondary outcome included the same indices plus coronary artery bypass grafting, carotid endartectomy, percutaneous coronary intervention, hospitalisation for congestive heart failure, peripheral vascular disease, or total mortality. We adjusted analyses for baseline differences in weight or fitness, demographic characteristics, and risk factors for cardiovascular disease. The Look AHEAD trial is registered withClinicalTrials.gov, numberNCT00017953 . Findings: For the analyses related to weight change, we excluded 311 ineligible participants, leaving a population of 4834; for the analyses related to fitness change, we excluded 739 participants, leaving a population of 4406. In analyses of the full cohort (ie, combining both study groups), over a median 10·2 years of follow-up (IQR 9·5–10·7), individuals who lost at least 10% of their bodyweight in the first year of the study had a 21% lower risk of the primary outcome (adjusted hazard ratio [HR] 0·79, 95% CI 0·64–0·98; p=0·034) and a 24% reduced risk of the secondary outcome (adjusted HR 0·76, 95% CI 0·63–0·91; p=0·003) compared with individuals with stable weight or weight gain. Achieving an increase of at least 2 metabolic equivalents in fitness change was associated with a significant reduction in the secondary outcome (adjusted HR 0·77, 95% CI 0·61–0·96; p=0·023) but not the primary outcome (adjusted HR 0·78, 0·60–1·03; p=0·079). In analyses treating the control group as the reference group, participants in the intensive lifestyle intervention group who lost at least 10% of their bodyweight had a 20% lower risk of the primary outcome (adjusted HR 0·80, 95% CI 0·65–0·99; p=0·039), and a 21% lower risk of the secondary outcome (adjusted HR 0·79, 95% CI 0·66–0·95; p=0·011); however, change in fitness was not significantly associated with a change in the primary outcome. Interpretation: The results of this post-hoc analysis of Look AHEAD suggest an association between the magnitude of weight loss and incidence of cardiovascular disease in people with type 2 diabetes. These findings suggest a need to continue to refine approaches to identify individuals who are most likely to benefit from lifestyle interventions and to develop strategies to improve the magnitude of sustained weight loss with lifestyle interventions. Funding: US National Institute of Diabetes and Digestive and Kidney Diseases.